The reduction reaction of carbon dioxide on a precise number of Fe atoms anchored on two-dimensional biphenylene. Issue 44 (7th November 2022) - Xing, Na; Liu, Ziyang; Wang, Zhongwei; Gao, Yan; Li, Qingfang; Wang, Haifeng
Abstract : The reduction reaction of carbon dioxide on a precise number of Fe atoms anchored on two-dimensional biphenylene. Abstract : In recent accomplishments, a new two-dimensional allotrope of carbon–biphenylene (BP) was experimentally synthesized [Fan et al., Science, 372, 852–856 (2021)]. The BP sheet is composed of four-, six-, and eight-membered carbon rings constructed using periodically arranged sp 2 -hybridized carbon atoms. Unlike semi-metallic graphene, BP is metallic with quite active atoms and chemical bonds, and the binding strength with reaction intermediates will be enhanced, which means that it may exhibit good catalytic activity in some electrochemical catalytic reactions. Using spin-polarized density functional theory based on first-principles simulations and ab initio molecular dynamic calculations, we systematically investigated the structure, thermodynamic stability, CO2 reduction reaction (CO2 RR) activity and product selectivity of a precise number of Fe n ( n = 1–3) atoms embedded on a BP monolayer. The calculated results indicate that our designed Fe1 @BP, Fe2 @BP and Fe3 @BP complexes possess good thermodynamic and electrochemical stabilities and strong absorption for CO2, which promotes the activation of CO2 . Furthermore, the Fe2 @BP catalyst possesses good catalytic ability for the CO2 RR to CH3 OH due to a small rate determining potential of −0.48 V. In addition, Fe2 - and Fe3 @BP catalysts demonstrate superior catalytic performance for the CO2 RR to CH4 with low rate-limiting steps. More importantly, both the Fe2 and Fe3 @BP catalysts can effectively suppress the hydrogen evolution reaction (HER) during the entire CO2 RR process. The electronic structure analysis shows that the enhanced ability of Fe1–3 @BP catalysts for effective CO2 reduction can be attributed to the establishment of strong hybridization between Fe–3d and O–2p or C–2p states, which is conducive to the transfer of strong electrons to the anti-bond orbital of CO2 . This work provides an in-depth insight into the intrinsic catalytic mechanisms of the CO2 RR on Fe1–3 @BP catalysts, and highlights the excellent performance of the BP sheet as a substrate material for the polyatomic catalyst.